2012
DOI: 10.1039/c1lc20727j
|View full text |Cite
|
Sign up to set email alerts
|

Parylene to silicon nitride bonding for post-integration of high pressure microfluidics to CMOS devices

Abstract: High pressure-rated channels allow microfluidic assays to be performed on a smaller footprint while keeping the throughput, thanks to the higher enabled flow rates, opening up perspectives for cost-effective integration of CMOS chips to microfluidic circuits. Accordingly, this study introduces an easy, low-cost and efficient method for realizing high pressure microfluidics-to-CMOS integration. First, we report a new low temperature (280 °C) Parylene-C wafer bonding technique, where O(2) plasma-treated Parylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…S3 of the Supplementary Information ), thereby forming 100-μm high and 250-μm wide microfluidic channels. The details of this fabrication technique can be found elsewhere 15 28 29 . The MTP formed a fluidic halve-chamber that was reversibly clamped with a tissue slide using the force provided by a permanent magnet ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…S3 of the Supplementary Information ), thereby forming 100-μm high and 250-μm wide microfluidic channels. The details of this fabrication technique can be found elsewhere 15 28 29 . The MTP formed a fluidic halve-chamber that was reversibly clamped with a tissue slide using the force provided by a permanent magnet ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This process provides a measured adhesion strength of 25 MPa between the patterned SU-8 layer and the glass cap. Although the prototype lab-on-CMOS device reported here incorporates traditional SU-8 microfluidic structures, many different methods can be adapted to form, for example, complex 3D architectures 19 or high pressure channels 20 .…”
Section: Integration Methodsmentioning
confidence: 99%
“…For example, Ciftlik et al reported bonding strength of 10 and 23 MPa after bonding Pyrex wafers to Parylene C layers deposited on silicon-oxide [108] and silicon-nitride (Fig. 5b) [109], respectively. The bonding technique developed in this work was later used in the fabrication of a high-pressure compatible microfluidic chip for immunohistochemical applications [110].…”
Section: Sealing Using Adhesive Layersmentioning
confidence: 98%
“…Here, a glass cover is bonded to the patterned Cu layer of a PCB (a) and a Pyrex wafer is bonded to a thin layer of silicon nitride on a Si wafer (b). (a) After[99] and (b) after[109]. (a) and (b) are reproduced with permission from Royal Society of Chemistry.…”
mentioning
confidence: 98%